Fixed Point Results of a General Class of Monotone Nonexpansive Mappings in Hyperbolic Metric Spaces - Rida Outass; Karim Chaira; El Miloudi Marhrani; Nour-eddine El Harmouchi (Journal of Function Spaces)
In this paper, we introduce and study some properties of a new class of generalized monotone nonexpansive mappings in hyperbolic metric spaces. Further, we give some results on the convergence of the Mann iterative process for this class of mappings in hyperbolic ordered metric spaces with some interesting examples.